Numerical and Analytical Modeling of Large Deflection with Local Indentation of Sandwich Beam Under Quasi-Static Transverse Loading - Mohammad Solooki (مجله مدل سازی در مهندسی)
By taking local indention effect and foam core strength into account in the overall deflection process, a novel theoretical model is investigated to predict the large deflection with local indentation of sandwich beam under quasi-static lateral loading. The theoretical and numerical models of lateral crushing force and total plastic energy are proposed and the theoretical results agree well with numerical and experimental results of previous researches. The results conclude that local indention phase plays an important role in initial collapse deflection of sandwich beam when maximum deflection is greater than face sheets thickness. In addition, the theoretical results with and without local indention phase of total plastic energy are compared and it shows that total plastic energy of sandwich beam will be overestimated if local indention phase is neglected. The present analytical model can predict the large deflection behavior with local indention of sandwich beam reasonably.